Old cowboys never die [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Old cowboys never die, 2023)
"After thirty hard years of chasing stampedes into storms and pushing herds of half-crazy cows across the plains, longtime buddies and cattle drivers Casey Tubbs and Eli Doolin are ready to hang up their spurs. But when they get to Abilene with their final delivery of two thousand cows, the company lawyer has skipped town with their crew's entire wages. That means there's just one last job Eli and Casey will have to do... Steal it back. Sure, pulling off a robbery is a new challenge for these old boys. But they've learned a lot of tricks over the years --and they're one hell of a team. Between the two of them, they devise a scheme to hold up the lawyer on the noon train and deliver the money to the men who earned it. Except after pulling off the perfect crime--and getting away with it--an honest, peaceful retirement stops sounding so good. Casey and Eli start thinking they may have missed their calling in life. This could be the start of a whole new career . . . as outlaws"--